A Proposed Model for Antecedents and Consequences of Green Organizational Culture for Employees in the Public and Private Manufacturing Industry Sectors in Egypt - Abou Al Nile, Reem Ahmed; Abdel-shakoor, Hany Mohamed Galal (The Arab Journal of Administration, 2025)
Currently, there has been an increasing attention paid to employees’ behavior in the organization as a driving force of environmental issues. Consequently, organizations are adopting several environmental protection initiatives and developing green organizational strategies. Despite the growth of research in this field, the antecedents and consequences of green organizational culture are still calling for further investigation. In responding to that, this study contributes to the literature by investigating the determinants and outcomes of green organizational culture. This research used a statistical analysis to measure and evaluates how the three antecedents’ green human resource, green leadership and green environmental concerns have a positive impact on green organizational culture, Furthermore the significant impact of green organizational culture on green employees’ behavior and organization environmental performance. By employing the quantitative research design, the data was collected from 384 respondents as a sample size. A closed ended questionnaire was used to collect data from public and private sectors of the manufacturing industry in Egypt. The Partial Least Squares Structural Equations Modeling technique is used to verify the research framework. The findings confirmed the positive impact of green human resource management, green leadership behavior and environmental concern on green organizational culture. Furthermore, green organizational culture was confirmed to have a significant positive impact on employees’ green behavior and organizational environmental performance. This research contributes to the current literature on green organizational culture by examining these impacts and testing them. It also offers guidelines for leadership and decision maker on how to enhance their green human resource, green leadership behavior and environmental concerns to raise their green organizational culture which in consequences maximize employees’ green behavior in their organization and subsequently create a culture of environmentally friendly organization.